A limit on the diffuse gamma-rays measured with KASCADE-Grande. (July 2015) - Kang, D; Apel, W D; Arteaga-Velázquez, J C; Bekk, K; Bertaina, M; Blümer, J; Bozdog, H; Brancus, I M; Cantoni, E; Chiavassa, A; Cossavella, F; Daumiller, K; et al.
Abstract: Using data measured by the KASCADE-Grande air shower array, an upper limit to the flux of ultra-high energy gamma-rays in the primary cosmic-ray flux is determined. KASCADE-Grande measures the electromagnetic and muonic components for individual air showers in the energy range from 10 PeV up to 1 EeV. The analysis is performed by selecting air showers with low muon contents. A preliminary result on the 90% C.L. upper limit to the relative intensity of gamma-ray with respect to cosmic ray primaries is presented and compared with limits reported by other measurements.